Aspects of Legal Certainty in the Unilateral Cancellation of Notarial Deeds without the Presence of the Interested Party - Sudiro, Amad; Dilla, Shinta (JURNAL AKTA, 2025)
The aim of this study is to discuss the Aspect of Legal Certainty in the Unilateral Cancellation of Notarial Deeds Without the Presence of Interested Parties, in which one form of legal certainty is Legislation. Furthermore, in order to guarantee legal certainty if there is a contract between legal subjects which requires further legal action, it is usually conducted by making an official deed made before a notary. The position and legal force of a notarial deed are important since notaries are given special authority by special laws so that the notary's responsibility for the cancellation of a deed needs to be further analyzed because it is an inseparable aspect of legal certainty in the civil law system in Indonesia. This study used normative research by using the approach method, theory/concept, and analysis method included in the discipline of dogmatic law by analyzing the decision of case Number: 1127/Pdt.G/2020/PN. Dps Data were collected through literature study and it was analyzed descriptively qualitatively with primary legal materials and secondary legal materials. This study concludes that a notarial deed will be an authentic deed if the deed is made in accordance with existing regulations and it meets the provisions stipulated in the Notary Law and the notary's responsibility in cancelling a notarial deed conducted unilaterally without the presence of a notary.